PENGARUH MINAT BELAJAR SISWA TERHADAP KEAKTIFAN BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA AL – CHASANAH TANJUNG DUREN JAKARTA BARAT - Nisrina; Susanto, Heru (LP2M JAMIAT KHEIR, 2025)
This research aims to determine learning interest, learning activeness, and the influence of students' learning interest on learning activeness in Islamic Religious Education at SMA Al Chasanah Tanjung Duren, West Jakarta. Learning interest is viewed as an important factor that influences the level of student activeness in the learning process. The method used was a quantitative approach with an ex-post facto design. Data were collected through questionnaires from 46 students as samples and analyzed using empirical mean, theoretical mean, Pearson Product Moment correlation, simple linear regression, and F-test formulas. The research results show that both learning interest and learning activeness are in the good category, with averages of 61.48 and 63.82, higher than the theoretical mean of 50. The correlation coefficient of 0.7633 indicates a positive and strong relationship between learning interest and student learning activeness. The linear regression equation obtained is Y = 17.231 + 0.757908x with an F-test of 76.4066, proving that the influence of learning interest on learning activeness is statistically significant. The coefficient of determination (R²) of 63.46% indicates that learning interest explains the majority of the variance in learning activeness, while the remainder is influenced by other factors outside this study, such as students who prefer economics, mathematics, English, and other subjects. These findings reinforce the theory that interest is an important internal factor that encourages active student participation. In conclusion, increasing learning interest needs serious attention to enhance student learning activeness so that the Islamic Religious Education learning process at SMA Al Chasanah.